(untitled) (Geo-Eco-Marina, 2023)
The Browse Basin, now part of Australia`s North West Shelf passive margin, was formed through six major tectonic events, from the Paleozoic to the Miocene, and is a gas and condensate rich province in north-west Australia. In this study we focused on Eocene-Oligocene stratigraphic plays in order to extend the basin`s resources by proposing new prospects that could include reservoirs with both liquid and gaseous hydrocarbons. Lithologic descriptions from wells, structural and depth maps, along with seismic attributes (GSD and RMS Amplitude), were integrated to create a sedimentological model for the of the Prion Fm. We highlighted the fact that the distal zones of the upper part of the Upper Eocene – Lower Oligocene sequence host multiple individual, disconnected, submarine fan systems that create the proper framework for the exploration activity. An interesting prospect was proposed in this project, one that might yield recoverable resources of around 31 MMbbl of oil and 236 BCF of gas (solution gas and free gas cumulated) (Pmean values for estimates). This is an attempt to unlock oil reserves that currently lack throughout the region.